Digital Transformation Through SI DESA: Improving the Quality of Public Services and the Welfare of Local Business Actors in Candirejo Tourism Village - Budiantoro, Risanda A.; Susanti, Anis; Putra, Febrianur I.F.S.; Himmatina, Dina N.; Kholifah, Miftakhul JN; Cahyani, Indah A.; Zahra, Mauren A.; Latifah, Faela R.; Ali, Luthfi G. (Universitas Pendidikan Ganesha, 2025)
Candirejo Tourism Village has significant tourism and cultural potential. However, the main challenge faced is the lack of an integrated information system. This study aims to develop a Village Information System (SI Desa) to improve the quality of public services and the efficiency of economic actors' businesses and encourage sustainable welfare. This study uses a qualitative descriptive research type. Data were collected through observation, interview, and survey methods to 15 business actors and cooperative administrators in Candirejo Village who were involved in the training and mentoring program for the use of SI Desa. Data analysis was carried out using a descriptive approach. The results of the study showed that the implementation of SI Desa significantly increased public access to public services and business welfare, as evidenced by the increase in the service access index from 57.14% (quite good) to 80.02% (very good). This program supports the achievement of several Village SDGs, such as poverty eradication (SDGs 1), inclusive economic growth (SDGs 8), and strong institutions (SDGs 16). It is hoped that the development of this Village SI will create an inclusive village digital ecosystem, strengthen community participation, and increase the competitiveness of micro-businesses in Candirejo Tourism Village.